Empowerment of women as head of poor family through the P2WKSS program in Bekasi City - Noer, Khaerul Umam (Community Empowerment, 2021)
Poverty is a condition of economic inability to meet the average standard of living of the community. This condition is exacerbated when women become the head of the family where they are not only responsible for domestic roles, but also fulfill all the needs of their family members. One of the efforts of the Bekasi City government to reduce poverty is by running an integrated program of Increasing the Role of Women Towards a Healthy and Prosperous Family (P2WKSS). P2WKSS is a program to improve the quality of life of women in the aspects of education, health and purchasing power, especially for poor families in villages. Using the Participatory Action Research method and the seven-stage community empowerment analysis model, this paper focuses on how to encourage P2WKSS as an answer to improving the welfare of women heads of poor families. This activity strengthens the contribution of P2WKSS activities in providing additional household economic income which directly improves the welfare of poor families.